2019
DOI: 10.3390/antibiotics8030142
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Appropriate Antibiotic Use in Bacteremia Patients Presenting at the Emergency Department

Abstract: Sepsis is a condition that requires appropriate antibiotic treatment at the emergency department (ED). Most previous studies conducted on inappropriate antibiotic use at the ED were conducted in developed countries with a low percentage of sepsis. This study aimed to find additional clinical predictors for appropriate antibiotic use in bacteremia patients presenting at the ED from a developing country, in which there is a higher proportion of patients with sepsis. We included adult patients who presented at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The most frequently isolated Gram-positive bacteria were Enterococcus faecium (20%), Staphylococcus aureus (15%), and Staphylococcus epidermis (15%) in peripheral blood, and Enterococcus faecium (45.5%) in sterile body fluids and other sterile tissues. The most frequently isolated fungi was Candida albicans (50%) in peripheral blood samples of patients with BSI, which is consistent with previous publications [ 19 ]. Pneumocystis jirovecii (69.6%) was the main pathogen found in sterile body fluids and other sterile tissues, which was significantly different from the common fungal pathogen in BSIs.…”
Section: Resultssupporting
confidence: 91%
“…The most frequently isolated Gram-positive bacteria were Enterococcus faecium (20%), Staphylococcus aureus (15%), and Staphylococcus epidermis (15%) in peripheral blood, and Enterococcus faecium (45.5%) in sterile body fluids and other sterile tissues. The most frequently isolated fungi was Candida albicans (50%) in peripheral blood samples of patients with BSI, which is consistent with previous publications [ 19 ]. Pneumocystis jirovecii (69.6%) was the main pathogen found in sterile body fluids and other sterile tissues, which was significantly different from the common fungal pathogen in BSIs.…”
Section: Resultssupporting
confidence: 91%
“…Factors with a p-value of less than 0.25 in univariate analysis were subsequently included in the logistic regression analysis to determine predictors of inappropriate antibiotic choice. 39 The Hosmer-Lemeshow method was used to test for goodness of fit for the model. An a priori alpha (α) of 0.05 was used to define statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…In the United States, at least one antibiotic is prescribed to around 7% to 8% of cases admitted to the ED on a daily basis (Harrison and Ouyang, 2013). Phungoen et al (2019) studied patients who were admitted to the ED having sepsis. It was found that almost a fifth (17%) of the ED admitted patients received inappropriate antibiotics and resulted in a longer stay in the hospital and an increased mortality rate.…”
Section: Introductionmentioning
confidence: 99%